Getting to Know You: Trust Formation in New Interfirm Relationships and the Consequences for Investments in Management Control and the Collaboration - Anderson, Shannon W.; Chang, Hwei Fern; Cheng, Mandy M.; Phua, Yee Shih (Contemporary Accounting Research, 2017)
Abstract Trust is often posited to substitute for management control in interfirm transactions. However, this raises questions of how trust arises in new relationships, and whether trust that is not based on prior experience transacting together is sufficient to persuade managers to forgo investments in management controls. We use an experiment to test whether two features of the early stage of an interfirm relationship influence a buyer's initial trust in a supplier and have consequences for subsequent investments in management controls and in the collaboration. These two features are the autonomy of the buyer's manager to choose a supplier (i.e., delegation of decision‐making authority) and the supplier's willingness to share information with the buyer. We find that the buyer manager's initial trust in the supplier is associated positively with both the autonomy to choose the supplier and the supplier's willingness to share information. Information content and supplier characteristics are held constant, so these results are novel and distinct from prior studies of the antecedents of trust. We find that higher initial trust is associated with reduced expenditures for management controls and increased investments in the collaboration. Thus, we conclude that delegation of decision‐making authority and supplier information‐sharing behavior in the early stages of a relationship influence the formation of initial trust, which has real consequences for investments in management control and in the collaboration.